Management of Cardiovascular Medicines at the Regional Diagnostic Treatment Centers of Mongolia - Lkhagvasuren, Dulmaa; Dorjbal, Enkhjargal (Caucasus Journal of Health Sciences and Public Health, 2020)
Cardiovascular diseases(CVDs) are the great public health problem.Thus the management and rational use of cardiovascular medicinesshould attract a focused attention. We aimed to identify cardiovascular medicines needing strict management control, used at the three Regional Diagnostic Treatment centers.